IMPLEMENTASI PEMBIASAAN SHOLAT DHUHA UNTUK MENINGKATKAN PEMBELAJARAN RELIGIUS DI SMA MA’ARIF LAWANG MALANG - Ahmad Ma’ruf (Journal Multicultural of Islamic Education, 2022)
The implementation of the habit of dhuha prayer is carried out every Monday and Thursday, in addition to that day at the Maarif Lawang High School prayer room it is carried out in congregation in each class led by the students themselves, and those who get the task of being prayer priests and other students become ma’mum. Meanwhile, students are required to be more independent, so that students can be more mastered in reciting the Dukha prayer and can carry out until adulthood. From the results of the study, it was found several notes for each student, and had a journal book for dhukha prayers starting from class X to class XII regularly. In a day only for one class, and which is carried out on every Monday while those who work are students of class X, while those who make the schedule for the priestly dhukha prayer are left to the students by deciding on one of the students, with the order of the students' seats. , the determination of the attendance list so that all students are better prepared. Because each class is carried out individually and is led by representatives of students who have been systematically scheduled.